The Effects of Noticing Training on Malay ESL Learners’ Use of Past Time Forms in Writing - Mohammad Lotfie, Maskanah (2007)
This study investigates the role of noticing in improving written accuracy. The noticing hypothesis focuses on the need to enhance learners’ awareness of target language forms in order to convert input into intake and to subsequently internalise input as part of interlanguage. This study also takes into account the comprehensible output hypothesis that proposes that output can promote noticing as it encourages learners to become aware of the gap between their interlanguage and the target language usage. These concepts together with elements from the process approach to writing have been translated into three types of feedback techniques for ESL learners’ written output. The techniques are Enhancement, Reformulation, and the Sequential technique. All three techniques function as a means of enhancing learners’ awareness of past time forms and are, therefore, form-focused in nature but do not involve explicit explanations of those target forms. The study has adopted a mixed approach design that is both confirmatory and interpretative. A quasi-experiment that tested the effects of the instructional techniques involved 81 matriculation (post-secondary) students from three groups. Qualitative procedures included the collection of think aloud protocols which were administered to investigate learners’ cognitive responses to the instructional techniques. A content analysis of written output identified the learners’ patterns of past time form acquisition. An attitude survey gauged the learners’ affective perceptions of instruction. Respondents in the Enhancement group tended to produce non-metalingual reponses during the think aloud procedure. On the other hand, the respondents from the Reformulation group produced more metalingual responses. Results suggest that noticing is influenced by the types of learner responses to the techniques. The analysis of the think aloud protocols and the essays of the Enhancement group indicate that the respondents may have corrected errors while responding to the treatment, but failed to do so in the subsequent essays. Similarly in the Reformulation group, awareness of why a form is corrected may not result in corrected forms in the second essay. In other words, correct responses to treatments do not necessarily ensure subsequent correct usage of the forms. There is also evidence that the structural features of a target form influence the success of the form being noticed. The simple simple past from was easily noticed than the more complex present perfect form with its auxiliaries and past participles. Statistical results obtained through the applications of pairedsamples t tests and ANCOVA suggest that all three instructional techniques were successful in enhancing noticing and in increasing learners’ written accuracy. The learners who participated in the study perceived the instructional interventions favourably. The study indicates that form-focused techniques should be incorporated as part of ESL course syallabuses and that the techniques should be included in writing courses. Instruction should also include output-based input that can authentically point out to ESL instructors individualised accuracy-related problems in their students’ written work. The complex tense-aspect temporal references to the past is an area of the English language system that would need more focus at the post-secondary level. This study has managed to further refine the concept of noticing in SLA. It shows that the types and effectiveness of noticing are influenced by the nature of input, stimuli, selection of target forms and learner backgrounds. Noticing is, indeed, an important process in an ESL learner’s journey to acquire linguistic items. Instructional interventions that try to enhance noticing in relation to written accuracy should effectively help students as they continue to develop their interlanguage.